The Etymological Background of the English Vocabulary - Kalantarova Nazokat Kadambayevna (Zien Journals, 2022)
Etymology is the study of the history of words, their origins, and how their form and meaning have changed over time. By extension, the term "the etymology (of a word)" means the origin of the particular word.
Keywords: etymologists; written history; reconstruct information